Carta del Concejo Municipal de San Juan a Roberto H.Todd - Todd, Roberto H.; Fernández, Jas; Sánchez, Miguel; López Castro, B.; Moraza, Manuel; Laloma, Francisco; Cintrón, Blas; Pérez Villar, Manuel (My University, 1905)
Carta felicitando a Todd por su nombramiento para alcalde.
Keywords: Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.; Fernández, Jas--Correspondence.; Fernández, Jas--Correspondencia.; Sánchez, Miguel--Correspondence.; Sánchez, Miguel--Correspondencia.; López Castro, B.--Correspondence.; López Castro, B.--Correspondencia.; Moraza, Manuel--Correspondence.; Moraza, Manuel--Correspondencia.; Laloma, Francisco--Correspondence.; Laloma, Francisco--Correspondencia.; Cintrón, Blas--Correspondence.; Cintrón, Blas--Correspondencia.; Perez Villar, Manuel--Correspondence.; Perez Villar, Manuel--Correspondencia.